THE INFLUENCE OF ELECTRONIC WORD OF MOUTH AND SOCIAL MEDIA MARKETING ON BRAND IMAGE AND PURCHASE INTENTION OF E-COMMERCE COSMETIC PRODUCTS - Jayad, Ismed; Wahyu, Agung; Sumardi (PENANOMICS: International Journal of Economics, 2023)
In the digital age, electronic word of mouth (eWOM) and social media platforms have dramatically transformed consumer behavior and marketing strategies. This study explores the impact of eWOM and social media marketing on brand image and consumer purchase intentions within the e-commerce cosmetic market in Indonesia. The study aims to understand the mechanisms through which these digital marketing strategies affect consumer perceptions and behaviors in a local cultural context. Using a quantitative causality research approach, the study sampled 260 respondents through purposive sampling and employed SEM-PLS for data analysis. The findings reveal that both eWOM and social media marketing significantly enhance brand image, which in turn positively influences purchase intentions. However, social media marketing alone did not show a significant direct effect on purchase intentions, highlighting the mediating role of brand image. This research provides valuable insights for marketers to optimize digital strategies, enhance consumer engagement, and build a competitive edge in the e-commerce cosmetic market.